Optimization of supercritical CO2 extraction of fish oil from viscera of African catfish (Clarias gariepinus) - Sarker, Md. Zaidul Islam; Selamat, Jinap; Md. Ahsan Habib, Abu Sayem; Ferdosh, Sahena; Akanda, Mohamed Jahurul Haque; Mohamed Jaffri, Juliana (MDPI, 2012)
Fish oil was extracted from the viscera of African Catfish using supercritical carbon dioxide (SC-CO2). A Central Composite Design of Response Surface methodology (RSM) was employed to optimize the SC-CO2 extraction parameters. The oil yield (Y) as response variable was executed against the four independent variables, namely pressure, temperature, flow rate and soaking time. The oil yield varied with the linear, quadratic and interaction of pressure, temperature, flow rate and soaking time. Optimum points were observed within the variables of temperature from 35 °C to 80 °C, pressure from 10 MPa to 40 MPa, flow rate from 1 mL/min to 3 mL/min and soaking time from 1 h to 4 h. However, the extraction parameters were found to be optimized at temperature 57.5 °C, pressure 40 MPa, flow rate 2.0 mL/min and soaking time 2.5 h. At this optimized condition, the highest oil yields were found to be 67.0% (g oil/100 g sample on dry basis) in the viscera of catfish which was reasonable to the yields of 78.0% extracted using the Soxhlet method.